2016
DOI: 10.1093/jmicro/dfv375
|View full text |Cite
|
Sign up to set email alerts
|

Motion analysis and ultrastructural study of a colonial diatom,Bacillaria paxillifer

Abstract: The pennate diatom, Bacillaria paxillifer, forms a colony in which adjacent cells glide smoothly and almost continuously, yet no obvious apparatus driving the movement, such as flagella or cilia, is observed. Thus far, neither the mechanism nor physiological significance of this movement has been well understood. Here, we report quantitative analysis of the gliding motion of B. paxillifer and morphological analysis of this diatom with light and electron microscopes. The gliding of pairs of adjacent B. paxillif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Vertical community migration movements upward and downward are typically completed in 20 min (Hopkins and Drum, 1966 and references therein) but recently Cartaxana et al (2016) reported the beginning of downward migration almost 2 h before tidal flooding. Maximum gliding speed reported for diatoms was ∼20 µm s −1 (Yamaoka et al, 2016) (Table 1), but this was attained in the very specific situation of gliding in the colonial species Bacillaria paxillifera. Murase et al (2011) refer maximum gliding speed an order of magnitude lower (1-2 µm s −1 ) and Wang et al (2013) cast doubts in the capacity of the 2016Bacillaria paxillifera 20 Colonial diatom; adjacent cells glide over each other Kooistra et al (2003) Toxarium undulatum 3.5 Maximum speed of 6 µm s −1 was observed, but only for 10 s; speeds of 0.5-2 µm s −1 were more common.…”
Section: Vertical Movements On Microphytobenthosmentioning
confidence: 99%
See 3 more Smart Citations
“…Vertical community migration movements upward and downward are typically completed in 20 min (Hopkins and Drum, 1966 and references therein) but recently Cartaxana et al (2016) reported the beginning of downward migration almost 2 h before tidal flooding. Maximum gliding speed reported for diatoms was ∼20 µm s −1 (Yamaoka et al, 2016) (Table 1), but this was attained in the very specific situation of gliding in the colonial species Bacillaria paxillifera. Murase et al (2011) refer maximum gliding speed an order of magnitude lower (1-2 µm s −1 ) and Wang et al (2013) cast doubts in the capacity of the 2016Bacillaria paxillifera 20 Colonial diatom; adjacent cells glide over each other Kooistra et al (2003) Toxarium undulatum 3.5 Maximum speed of 6 µm s −1 was observed, but only for 10 s; speeds of 0.5-2 µm s −1 were more common.…”
Section: Vertical Movements On Microphytobenthosmentioning
confidence: 99%
“…where σ ∼ 1 in the case of highly directional vertical motion and σ ≫ 1 for the case of highly chaotic or bidirectional-gliding motion (Yamaoka et al, 2016). Concrete estimations of E S h x(s), y(s), z(s) , as well as σ and A m , may be obtained on the basis of various stochastic models describing, to one degree or another, the real movement of different types of diatoms in accordance to their "decision making" and the sediment granularity or by analysis of recorded diatom tracks.…”
Section: Assessment Of the Depth-to-surface Path Lengthmentioning
confidence: 99%
See 2 more Smart Citations
“…that each colony is a multicellular organism). Cellular biology work that has been done on the movement of Bacillaria [6][7][8], is neither computational in nature nor at the whole-organism level.…”
Section: Introductionmentioning
confidence: 99%